Different Plant Species Have Common Sequence Features Related to mRNA Degradation Intermediates. (10th September 2019) - Ueno, Daishin; Mukuta, Takafumi; Yamasaki, Shotaro; Mikami, Maki; Demura, Taku; Matsui, Takeshi; Sawada, Kazutoshi; Katsumoto, Yukihisa; Okitsu, Naoko; Kato, Ko
Abstract: mRNA degradation is an important cellular mechanism involved in the control of gene expression. Several genome-wide profiling methods have been developed for detecting mRNA degradation in plants and animals. However, because many of these techniques use poly (A) mRNA for library preparation, degradation intermediates are often only detected near the 3′-ends of transcripts. Previously, we developed the Truncated RNA End Sequencing (TREseq) method using Arabidopsis thaliana, and demonstrated that this method ameliorates 3′-end bias. In analyses using TREseq, we observed G-rich sequences near the 5′-ends of degradation intermediates. However, this finding remained to be confirmed in other plant species. Hence, in this study, we conducted TREseq analyses in Lactuca sativa (lettuce), Oryza sativa (rice) and Rosa hybrida (rose). These species including A. thaliana were selected to encompass a diverse range in the angiosperm phylogeny. The results revealed similar sequence features near the 5′-ends of degradation intermediates, and involvement of translation process in all four species. In addition, homologous genes have similar efficiencies of mRNA degradation in different plants, suggesting that similar mechanisms of mRNA degradation are conserved across plant species. These strong sequence features were not observed in previous degradome analyses among different species in plants.